Editorial: Transhumanist Politics, Education, and Design - Jörgen Skågeby; Mattias Arvola; Lina Rahm (Linköping University Electronic Press, 2016)
This special issue of Confero takes its start in an essay by John Mazarakis who presents an overarching perspective on the underpinning politics of transhumanism. Considering theoretical debates and differences in the transhumanist movement over the last two decades, Mazarakis proposes the emergence of two distinct political stances: the techno-progressive and the technolibertarian. Using Lyotardian concepts, Mazarakis questions the latent legacy of "the grand narratives of modernism" and their potential to function as a basis for theorizing a transhuman future.